Effects of Combined Trigona Honey and Propolis on Oxidative Stress and Inflammation Biomarkers in Diabetes Models as an Anti-Aging Approach: A Systematic Literature Review - Herlina Setiawati; Agus Eka Darwinata (Eduvest - Journal of Universal Studies, 2026)
Aging is a complex biological process closely associated with oxidative stress and chronic inflammation, playing a critical role in the pathogenesis of metabolic diseases such as diabetes mellitus. Bee products, particularly Trigona honey and propolis, have been identified as sources of bioactive compounds with significant antioxidant and anti-inflammatory potential. This study aims to systematically evaluate the effects of stingless bee honey (Trigona sp.) and propolis on oxidative stress and inflammatory biomarkers within an anti-aging mechanistic framework in diabetes models. A systematic literature review following PRISMA 2020 guidelines was conducted on articles published between 2014 and 2024 from Scopus, PubMed, ScienceDirect, and Google Scholar. The PICO framework was applied for study selection, with dual independent reviewers. Of 2,219 identified articles, 40 studies met the inclusion criteria, comprising 28 in vivo, 8 in vitro, and 4 clinical studies. Trigona honey consistently reduced malondialdehyde (MDA) levels and enhanced superoxide dismutase (SOD) activity via KEAP1-NRF2 pathway activation. Propolis demonstrated dominant anti-inflammatory effects through NF-κB inhibition, significantly reducing interleukin-6 (IL-6) and tumor necrosis factor-alpha (TNF-α). Trigona honey and propolis exhibit complementary mechanisms that are promising as a multi-target approach in modulating aging biomarkers, and their combination potentially produces synergistic effects through dual-pathway modulation. Controlled clinical trials are warranted for further validation.